2022
DOI: 10.1515/ntrev-2022-0486
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of pure nanofluid (GO/engine oil) and hybrid nanofluid (GO–Fe3O4/engine oil): Novel thermal and magnetic features

Abstract: Hybrid nanofluids can provide better physical strength, thermal conductivity, and mechanical resistance in many thermodynamic systems than pure nanofluids. To establish the novel results, using superior types of hybrid nanoparticles like graphene oxide (GO) and iron oxide (Fe3O4) is the main focus of recent work. This study investigates the innovative thermal and magnetic features of both pure nanofluid GO/engine oil (EO) and hybrid nanofluid GO–Fe3O4 /EO under the simultaneous effects of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Nawaz et al [19] studied the hybrid Williamson nanofluid following the non-Fourier heat conduction and Forchheimer porous medium. The most recent study is by Sohail et al [20] examined the thermal and flow characteristics of the hybrid and single-phase GO EO / and Fe O GO EO…”
Section: Introductionmentioning
confidence: 99%
“…Nawaz et al [19] studied the hybrid Williamson nanofluid following the non-Fourier heat conduction and Forchheimer porous medium. The most recent study is by Sohail et al [20] examined the thermal and flow characteristics of the hybrid and single-phase GO EO / and Fe O GO EO…”
Section: Introductionmentioning
confidence: 99%
“…Some works have already been devoted to the study of the use of hybrid nanoparticles in lubricating oils. For instance, Ahmad et al [15] investigated the thermal and magnetic characteristics of a nanofluid in motor oil (EO) with graphene oxide (GO), and the hybrid nanofluid GO-Fe 3 O 4 /EO under the same effect of the induced applied magnetic field. They observed that the hybrid GO-Fe 3 O 4 /EO composition provided the thermal stability of the nanofluids at high temperature.…”
Section: Introductionmentioning
confidence: 99%